Pengaruh Strategi Synergetic Teaching Pada Mata Pelajaran PAI Materi Kewajiban Menuntut Ilmu Terhadap Hasil Belajar Siswa Kelas X SMA Negeri 1 Bahorok - Indryani, Ainun Jannah; M, Mahariah; M, Miswar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study was conducted based on the problem of low student learning outcomes due to the Islamic Religious Education learning process which tends to be passive because in the learning process that occurs the teacher always uses conventional strategies. This study aims to determine whether the application of the synergetic teaching learning strategy has an effect on student learning outcomes in the Islamic Religious Education subject of class X SMA Negeri 1 Bahorok. The research method used is a quantitative approach with a quasi-experimental design in the form of a nonequivalent control group design. The research conducted with this form has a sample consisting of an experimental group and a control group of 72 students. The research instrument used in data collection was a multiple-choice learning outcome test. The data analysis technique in this study used the t-test type of independent sample t-test which must first meet the analysis prerequisite test in the form of a normality test and a homogeneity test. Hypothesis testing in this study used the independent t-test so that the results of t count (3.044)> t table (2.030) were obtained which means that H0 was rejected and Ha was accepted. The research findings show that there is a significant influence of the synergetic teaching strategy on student learning outcomes in the Islamic Religious Education subject. So that the learning process using active, innovative, creative, and fun strategies is worthy to be implemented with the hope of improving student learning outcomes, especially in Islamic Religious Education subjects.